2005
DOI: 10.1523/jneurosci.0416-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amygdalo-Nigral Circuitry in Conditioning of a Visual Stimulus Paired with Food

Abstract: The amygdala central nucleus (CeA) plays an important part in associative learning. Although most research has focused on functions of its descending projections to brainstem areas involved in autonomic and somatomotor responses, the ascending projections of CeA also play critical roles in learning. For example, a CeA-nigrostriatal pathway is important for acquiring orienting responses (ORs) to conditioned stimuli (CSs) that signal food delivery. In this study, the function of this CeA-nigrostriatal pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
118
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 40 publications
(39 reference statements)
11
118
3
Order By: Relevance
“…Disconnection of the CeA and SNc prevented the normal acquisition of conditioned orienting to a visual cue paired with food (Lee et al, 2005). In the same study, the authors showed that the medial CeA cells retrogradely labeled from the SNc expressed an immediate-early gene, FOS, after conditioned orienting responses, demonstrating the direct involvement of the CeA to SNc projection in conditioned orienting.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Disconnection of the CeA and SNc prevented the normal acquisition of conditioned orienting to a visual cue paired with food (Lee et al, 2005). In the same study, the authors showed that the medial CeA cells retrogradely labeled from the SNc expressed an immediate-early gene, FOS, after conditioned orienting responses, demonstrating the direct involvement of the CeA to SNc projection in conditioned orienting.…”
Section: Discussionmentioning
confidence: 86%
“…A second series of sections was used for tyrosine hydroxylase (TH) immunoreactivity, to evaluate the lesions made to SNc DA cells. The assessment of TH immunoreactivity followed a standard immunohistochemical protocol for free-floating tissues (Lee et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, we did find the habenula to be functionally coupled with the amygdala, which has reciprocal connections with the substantia nigra (25). The substantia nigra is the main output of the LHb (5) and plays a crucial role in associative learning.…”
Section: Discussionmentioning
confidence: 92%
“…Although our data suggest that both the BLA and CeN likely use valence-independent neuronal circuits to produce changes in arousal, they may affect physiological, attentional, behavioral, and mnemonic processes differently via their distinct sets of efferent projections (47). For example, projections from the CeN to the substantia nigra may be important for conditioned orienting responses (48), whereas projections from the BLA through the stria terminalis may be important for modulation of some forms of positively and negatively valenced memories (5). It is also possible that projections from the BLA to the CeN coordinate or permit changes in aspects of emotional arousal (49).…”
Section: Discussionmentioning
confidence: 99%